Integrasi Media Digital dalam Pembelajaran PAI: Analisis Tantangan dan Peluang - Rohili, Rohili; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2026)
The digital era necessitates transformation in Islamic Religious Education (PAI) learning to remain relevant and engaging for students. This qualitative case study aims to comprehensively analyze the use of digital media in PAI learning, focusing on the challenges and opportunities that arise at SMP Negeri 1 Sukabumi City. Data were collected through in-depth interviews with the principal and PAI teachers, learning observations, and document studies. The research findings indicate that the school has established supportive policies and strong leadership commitment. Implementation in the classroom, although still at a supplementary stage utilizing presentations and videos, has successfully increased student engagement and learning motivation. However, this integration faces complex challenges, including infrastructure limitations, digital competency gaps, and the core dilemma of maintaining alignment with Islamic values. Teachers develop adaptive strategies such as blended learning and simple content curation. To achieve transformative integration, it is necessary to strengthen teacher competencies in Technological Pedagogical Content Knowledge (TPACK) within the PAI context, develop ethical guidelines for digital content curation, and design learning that deliberately bridges digital understanding with the practical application of values.